2018
DOI: 10.22581/muet1982.1804.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu and Zn Coated Urea on Eh, pH and Solubility of Cu and Zn in Rice Soils

Abstract: The concentration of Cu (Copper) and Zn (Zinc) decreases upon flooded conditions of rice soil. To assess the effects of flooding and application of Cu and Zn coated urea on changes in Eh, pH and solubility of Cu and Zn, a glasshouse experiment was conducted at Universiti Putra Malaysia. Rice plants (30 days old seedlings of type MR-219) on two soils (riverine and alluvium and marine alluvium) were transplanted. Nine treatments with variable rates and combinations of Cu and Zn coated urea were applied. The sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Babar et al (2019) reported that using controlled-release urea (CRU) in the form of encapsulated urea for wheat during the winter growing season significantly increased N-availability in soil and improved yield by 40.5%. A similar observation was also reported previously by Babar et al in 2018 where they applied coated urea; used palm stearin as a binder which was enriched with Cu and Zn (urease inhibitors) observed a positive effect on all the growth parameters and N-contents along with the chlorophyll contents in rice plants under acidic soil conditions of Malaysia. They have documented a 40% increase over control in rice yield.…”
Section: Discussionsupporting
confidence: 88%
“…Babar et al (2019) reported that using controlled-release urea (CRU) in the form of encapsulated urea for wheat during the winter growing season significantly increased N-availability in soil and improved yield by 40.5%. A similar observation was also reported previously by Babar et al in 2018 where they applied coated urea; used palm stearin as a binder which was enriched with Cu and Zn (urease inhibitors) observed a positive effect on all the growth parameters and N-contents along with the chlorophyll contents in rice plants under acidic soil conditions of Malaysia. They have documented a 40% increase over control in rice yield.…”
Section: Discussionsupporting
confidence: 88%
“…Zinc-coated urea decreases the pH of the soil, thus, it increases zinc availability in the rhizosphere. Babar et al (2018) observed the positive effect of Zn-coated urea in controlling the fluctuation of pH ranging from 6.0 to 6.5 in submerged paddy soils. Hence, Zn-coated urea as a mineralcoated fertilizer significantly maintains the soil pH around the optimal plant value of 6.5.…”
Section: E Ect Of Soil Ph On Coated Ureamentioning
confidence: 88%
“…The rate of breakdown of coated urea fertilizers containing Zn is mostly determined by soil temperature and density of soil microflora, and the duration is also determined by the activity of soil microbes (Yang et al, 2018). Zinc-coated urea reduces the rate of urea hydrolysis and serves as a urease inhibitor which increases crop growth and yield (Babar et al, 2018).…”
Section: E Ect Of Microbial Activity On Availability Of Coated Ureamentioning
confidence: 99%